2020
DOI: 10.1038/s41598-020-59019-x
|View full text |Cite|
|
Sign up to set email alerts
|

Targeted memory reactivation during sleep boosts intentional forgetting of spatial locations

Abstract: Although we experience thousands of distinct events on a daily basis, relatively few are committed to memory. the human capacity to intentionally control which events will be remembered has been demonstrated using learning procedures with instructions to purposely avoid committing specific items to memory. in this study, we used a variant of the item-based directed-forgetting procedure and instructed participants to memorize the location of some images but not others on a grid. these instructions were conveyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…We next considered the effects of TMR on memory effects produced by the TNT procedure. Two main hypotheses were tested: (a) whether TMR can further enhance memory-suppression that was established via no-think instructions during wake (e.g., 21 ); and (b) whether memory suppression could be applied de-novo during sleep to impair subsequent retrieval (e.g., 20 ). Testing these hypotheses made use of the three word-sets used for cuing during NREM sleep.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We next considered the effects of TMR on memory effects produced by the TNT procedure. Two main hypotheses were tested: (a) whether TMR can further enhance memory-suppression that was established via no-think instructions during wake (e.g., 21 ); and (b) whether memory suppression could be applied de-novo during sleep to impair subsequent retrieval (e.g., 20 ). Testing these hypotheses made use of the three word-sets used for cuing during NREM sleep.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of our study was to consider the effects of targeted reactivation on memory suppression. Two previous studies have successfully used TMR to enhance memory suppression using cues associated with suppression in the context of directed forgetting tasks (in which participants are instructed not to commit recently presented information to memory 20 , 21 ). The mechanism enabling this suppressive effect is unknown, but it may involve a reactivation of the suppressive context conjointly with a specific memory, thereby consolidating an inhibitory memory trace which counteracts its subsequent expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies using cueing procedures (or "targeted memory reactivation") have suggested that task-or stimulus-specific neural reactivation early in the sleep night or during a nap enhances memory consolidation 9,[20][21][22] . Although our participants did not spent a full night of sleep in the scanner, we tentatively sought to test for such an effect.…”
Section: Task-related Neural Reactivation In Sleep Boosts Consolidationmentioning
confidence: 99%